Adhesive film for circuit connection, connection structure, and method for producing the same

By using the circuit connection adhesive film with thermosetting primary and secondary adhesive layers in the circuit connection, the buried rate and distribution of conductive particles are controlled, and the short circuit problem caused by the flow of conductive particles is solved, and a high-reliability circuit connection is achieved.

CN119790117APending Publication Date: 2025-04-08RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280099487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, the flow of conductive particles during circuit connection causes aggregation between electrodes, which may cause short circuits, and in high-density precision electronic devices, it is a challenge to effectively capture conductive particles to ensure connection reliability.

Method used

An adhesive film for circuit connection is adopted, which consists of a thermosetting primary adhesive layer and a secondary adhesive layer. The conductive particles are partially buried on one side of the primary adhesive layer. The flow rate of the adhesive layer reaches a specific ratio through specific crimping conditions and external stimulation curable composition to control the distribution and capture of conductive particles.

Benefits of technology

It effectively suppresses the rise of the connection resistance, ensures the capture of conductive particles, improves the reliability of circuit connections, and avoids the occurrence of short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790117A_ABST
    Figure CN119790117A_ABST
Patent Text Reader

Abstract

An adhesive film for circuit connection comprises: a first adhesive layer having thermosetting properties; conductive particles partially embedded in one side of the first adhesive layer; and a second adhesive layer having thermosetting properties and in contact with one side of the first adhesive layer, wherein the embedding rate of the conductive particles in the first adhesive layer is 30 to 90%, and the ratio of the flow rate of the second adhesive layer to the flow rate of the first adhesive layer is 1.20 to 4.00.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive film for circuit connection, a connection structure and a method for manufacturing the same. Background Art

[0002] In the past, various adhesive materials have been used for circuit connection. For example, as an adhesive material for connecting a liquid crystal display to a tape carrier package (TCP), connecting a flexible printed circuit (FPC) to a TCP, or connecting an FPC to a printed circuit board, an adhesive film for circuit connection in which conductive particles are dispersed is used. By using an adhesive film for circuit connection, it is possible to bond circuit components to each other while electrically connecting electrodes on the circuit components to each other via the conductive particles in the circuit connection portion.

[0003] In the field of precision electronic devices using adhesive films for circuit connection, the electrode width and the electrode interval have become very narrow as the circuit density has been advanced. Therefore, it is not necessarily easy to efficiently capture conductive particles on microelectrodes to obtain high connection reliability. In this regard, for example, Patent Document 1 proposes a method of separating conductive particles from each other by making conductive particles be biased to exist on one side of the adhesive film.

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2005 / 54388 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] However, in the method of Patent Document 1, since the conductive particles flow when the circuit is connected, the conductive particles aggregate between electrodes, which may cause a short circuit.

[0009] One aspect of the present invention is to provide an adhesive film for circuit connection that can suppress the increase in connection resistance and fully ensure the capture of conductive particles. Another aspect of the present invention is to provide a method for manufacturing the adhesive film for circuit connection. Other aspects of the present invention are to provide a connection structure using the adhesive film for circuit connection and a method for manufacturing the same.

[0010] Means for solving technical problems

[0011] Several aspects of the present invention provide the following [1] to

[16] . [1]

[0013] An adhesive film for circuit connection, comprising:

[0014] The first adhesive layer is thermosetting;

[0015] Conductive particles are partially embedded in one side of the first adhesive layer; and

[0016] a second adhesive layer having thermosetting properties and in contact with the one surface of the first adhesive layer,

[0017] The embedding rate of the conductive particles in the first adhesive layer obtained by the following formula (1) is 30 to 90%.

[0018] The circuit connection adhesive film is placed on a glass plate from the first adhesive layer side, and temporarily pressed under the conditions of a pressing temperature of 70°C, a pressing pressure of 0.1 MPa, and a pressing time of 1.0 s. Then, a glass plate is placed on the second adhesive layer, and formal pressing is performed under the conditions of a pressing temperature of 160°C, a pressing pressure of 2 MPa, and a pressing time of 5 s. The flow rate of each adhesive layer during formal pressing is defined by the following formula (2), and the ratio of the flow rate of the second adhesive layer to the flow rate of the first adhesive layer is 1.20 to 4.00.

[0019] Embedment rate (%) = H / L × 100 (1)

[0020] [In formula (1), H represents the embedding length of the conductive particles in the first adhesive layer (unit: μm), and L represents the particle size of the conductive particles in the embedding direction (unit: μm).]

[0021] Flow rate [%] = S B / S A ×100···(2)

[0022] [In formula (2), S A It represents the surface area of ​​the adhesive layer before temporary crimping, S B Indicates the area of ​​the adhesive layer after full crimping.] [2]

[0024] The adhesive film for circuit connection according to [1], wherein

[0025] The flow rate of the first adhesive layer is 88 to 110%. [3]

[0027] The adhesive film for circuit connection according to [1] or [2], wherein

[0028] The first adhesive layer is a cured product of a precursor layer containing an external stimulus curable composition. [4]

[0030] The circuit connection adhesive film according to [3], wherein:

[0031] The external stimulus curable composition has photocurability. [5]

[0033] The adhesive film for circuit connection according to any one of [1] to [4], wherein

[0034] At least a portion of the plurality of conductive particles are arranged in a predetermined pattern in a plan view. [6]

[0036] The adhesive film for circuit connection according to any one of [1] to [5], wherein

[0037] The average particle size of the conductive particles is 1.0 to 50.0 μm.

[0038] The CV value of the particle size of the conductive particles is 25% or less. [7]

[0040] The adhesive film for circuit connection according to any one of [1] to [6], wherein

[0041] The ratio of the thickness of the circuit-connecting adhesive film to the average particle diameter of the conductive particles is 1.1 to 10.0. [8]

[0043] The adhesive film for circuit connection according to any one of [1] to [7], wherein

[0044] The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer is 0.3 to 20.0. [9]

[0046] A method for producing a circuit-connecting adhesive film according to any one of [1] to [8], comprising:

[0047] Step (I) of preparing a first adhesive film including the first adhesive layer and the conductive particles partially embedded in one side of the first adhesive layer; and

[0048] Step (II), providing the second adhesive layer on the one side of the first adhesive layer,

[0049] The step (I) includes a curing step of curing the precursor layer by external stimulation to form the first adhesive layer in a state where the conductive particles are partially embedded in one surface side of the precursor layer including the external stimulation curable composition.

[10]

[0051] The method for producing an adhesive film for circuit connection according to [9], wherein:

[0052] In the curing step, the precursor layer is cured so that the flow rate of the first adhesive layer reaches 88 to 110%.

[11]

[0054] The method for producing an adhesive film for circuit connection according to [9] or

[10] , wherein:

[0055] The external stimulus curable composition has photocurability,

[0056] In the curing step, the precursor layer is cured by light irradiation.

[12]

[0058] The method for producing an adhesive film for circuit connection according to any one of [9] to

[11] , wherein:

[0059] The step (I) further includes a transfer step of transferring the conductive particles from the substrate to the precursor layer by providing the precursor layer on a surface of a substrate on which a plurality of conductive particles are arranged.

[13]

[0061] The method for producing an adhesive film for circuit connection according to

[12] , wherein:

[0062] The step (I) further includes a heating step of heating the layer containing the external stimulus curable composition at 50 to 70° C. for 3 to 60 minutes before the transfer step.

[14]

[0064] The method for producing an adhesive film for circuit connection according to

[12] or

[13] , wherein:

[0065] The step (I) further includes, after the transfer step, a pressurizing step of applying pressure to the surface of the precursor layer to which the conductive particles are transferred.

[15]

[0067] A connection structure, comprising: a first circuit component having a first electrode; a second circuit component having a second electrode electrically connected to the first electrode; and a connection portion, which electrically connects the first electrode and the second electrode to each other via conductive particles and bonds the first circuit component to the second circuit component.

[0068] The connecting portion includes a cured product of the circuit-connecting adhesive film according to any one of [1] to [8].

[16]

[0070] A method for manufacturing a connection structure, comprising the following steps:

[0071] The circuit-connecting adhesive film described in any one of [1] to [8] is disposed between a surface of a first circuit member having a first electrode and provided with the first electrode and a surface of a second circuit member having a second electrode and provided with the second electrode; and

[0072] The stack including the first circuit component, the circuit connection adhesive film and the second circuit component is heated while being pressed in the thickness direction of the stack, thereby electrically connecting the first electrode and the second electrode to each other via conductive particles and bonding the first circuit component to the second circuit component.

[0073] Effects of the Invention

[0074] According to one aspect of the present invention, there is provided an adhesive film for circuit connection that can suppress the increase in connection resistance and fully ensure the capture of conductive particles. Furthermore, according to another aspect of the present invention, there is provided a method for manufacturing the adhesive film for circuit connection. Furthermore, according to other aspects of the present invention, there is provided a connection structure using the adhesive film for circuit connection and a method for manufacturing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a schematic plan view showing one embodiment of the adhesive film for circuit connection.

[0076] Figure 2 is along Figure 1 A schematic cross-sectional view of the adhesive film for circuit connection taken along line II-II.

[0077] Figure 3 yes Figure 2 A partially enlarged view of the cross section of the circuit-connecting adhesive film shown.

[0078] Figure 4 This is a schematic diagram for explaining one embodiment of a method for producing an adhesive film for circuit connection.

[0079] Figure 5 This is a schematic diagram for explaining one embodiment of a method for producing an adhesive film for circuit connection.

[0080] Figure 6 This is a schematic diagram for explaining one embodiment of a method for producing an adhesive film for circuit connection.

[0081] Figure 7 This is a schematic diagram for explaining one embodiment of a method for producing an adhesive film for circuit connection.

[0082] Figure 8 It is a schematic cross-sectional view showing one embodiment of a connection structure.

[0083] Fig. 9 This is a schematic diagram for explaining one embodiment of a method for producing a connection structure. DETAILED DESCRIPTION

[0084] Hereinafter, the embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments. In addition, the materials exemplified below may be used alone or in combination of two or more unless otherwise specified. In the case where there are multiple substances equivalent to each component in the composition, the content of each component in the composition represents the total amount of the multiple substances present in the composition unless otherwise specified. The numerical range represented by "~" represents a range that includes the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage may be replaced by the upper limit or lower limit of the numerical range of other stages. In the numerical range recorded in this specification, the upper limit or lower limit of its numerical range may also be replaced by the value shown in the embodiment. In this specification, "(meth)acrylate" means at least one of acrylate and its corresponding methacrylate. The same is true in other similar expressions such as "(meth)acryloyl".

[0085] <Adhesive film for circuit connection>

[0086] The adhesive film for circuit connection includes conductive particles, a first adhesive layer having thermosetting properties, and a second adhesive layer having thermosetting properties. “Circuit connection” means used for connection of circuit components.

[0087] Figure 1 1 is a schematic top view showing one embodiment of an adhesive film for circuit connection. Figure 1There are a plurality of conductive particles 3 in the adhesive film 10 for circuit connection shown. Among the plurality of conductive particles 3, adjacent conductive particles 3 exist in a state separated from each other. Therefore, the adhesive film 10 for circuit connection can also have the property of being conductive in the pressurized direction and maintaining insulation in the non-pressurized direction (anisotropic conductivity). The ratio (monodispersity) of the conductive particles 3 existing in a state separated from other conductive particles 3 (monodisperse state) is preferably 90.0% or more, and can also be 93.0% or more, 95.0% or more, 97.0% or more, or 98.0% or more. The upper limit of the monodispersity is 100%. The higher the monodispersity, the easier it is to obtain a connection structure with excellent insulation reliability. In this dispersed state, it can be formed by using a substrate in which the conductive particles 3 are arranged in a prescribed arrangement in the manufacturing method of the adhesive film 10 for circuit connection. The details will be described later.

[0088] When the circuit connection adhesive film is viewed from above, at least a portion of the plurality of conductive particles 3 present are arranged in a predetermined pattern. The predetermined pattern (position and number of conductive particles 3) can be set, for example, according to the shape, size, and pattern of the electrodes to be connected. Figure 1 In the embodiment, the conductive particles 3 are arranged at regular and substantially uniform intervals in the entire area of ​​the adhesive film 10 for circuit connection, but the arrangement of the conductive particles 3 is not limited to this example. For example, when the adhesive film for circuit connection is viewed from above, the conductive particles 3 may be arranged in such a manner that a region where a plurality of conductive particles 3 are regularly arranged and a region where the conductive particles 3 are substantially absent are regularly formed. The arrangement of at least a portion of the plurality of conductive particles 3 in a predetermined pattern can be confirmed, for example, by observing the adhesive film 10 for circuit connection from above the main surface of the adhesive film 10 using an electron microscope or the like.

[0089] Figure 2 is along Figure 1 A schematic cross-sectional view of the adhesive film for circuit connection taken along line II-II, Figure 3 yes Figure 2 The partially enlarged view of the cross section of the circuit connection adhesive film shown. Figure 2 and Figure 3 In FIG. 1 , S represents the boundary between the first adhesive layer 1 and the second adhesive layer 2. Figure 3In the figure, C1 and C2 represent the two contact points between the surface of the conductive particle 3 and the boundary S, respectively, and l1 represents the line segment connecting the contact point C1 and the contact point C2 (the first virtual line segment). Also, l2 represents the line segment connecting the two points on the surface of the conductive particle 3 that is perpendicular to the line segment l1 and has the longest distance between the two points (the second virtual line segment). Also, C3 represents the contact point with the first adhesive layer 1 among the two points on the surface of the conductive particle 3 constituting the line segment l2, and C4 represents the contact point with the second adhesive layer 2. Also, the intersection of the line segment l1 and the line segment l2 is set to C5.

[0090] like Figure 2 and Figure 3 As shown in FIG. 1 , the conductive particles 3 are partially embedded in one side of the first adhesive layer 1, and the second adhesive layer 2 is arranged to be in contact with the first side of the first adhesive layer 1, so that the conductive particles 3 are covered by the first adhesive layer 1 and the second adhesive layer 2. The boundary S is located between adjacent conductive particles 3 and the separated portion of the conductive particles 3. Figure 2 In the embodiment, the plurality of conductive particles 3 are partially embedded in one side of the first adhesive layer 1, but as long as the effect of the present invention is not hindered, there may be conductive particles 3 completely embedded in the first adhesive layer 1 or the second adhesive layer 2. The proportion of conductive particles 3 completely embedded in the first adhesive layer 1 or the second adhesive layer 2 may be, for example, 20% or less, 10% or less, or 5% or less.

[0091] In the circuit-connecting adhesive film 10, the embedding rate of the conductive particles 3 in the first adhesive layer 1 (particle embedding rate) is 30 to 90%, and the ratio of the flow rate of the second adhesive layer 2 to the flow rate of the first adhesive layer 1 (hereinafter referred to as "flow ratio") is 1.20 to 4.00.

[0092] The particle embedding rate can be calculated by the following formula (1).

[0093] Particle embedding rate (%) = H / L × 100 (1)

[0094] In formula (1), H represents the embedding length of the conductive particle 3 in the first adhesive layer 1 (unit: μm), and L represents the particle size of the conductive particle in the embedding direction (unit: μm). In this specification, the direction perpendicular to the line segment l1 is set as the embedding direction of the conductive particle 3, and the maximum value of the particle size in the embedding direction is set as the particle size L of the conductive particle in the embedding direction. Therefore, the particle size L is equal to the length of the line segment l2. In addition, the maximum value of the length of the portion of the first adhesive layer 1 embedded in the conductive particle 3 (the length in the embedding direction) is set as the embedding length H of the conductive particle 3 in the first adhesive layer 1. Therefore, the embedding length H of the conductive particle 3 in the first adhesive layer 1 is equal to the length of the line segment connecting the contact point C3 and the intersection point C5.

[0095] The particle embedding rate can be measured, for example, by observing the longitudinal section (cross section in the thickness direction) of the circuit connection adhesive film through a scanning electron microscope (SEM). Specifically, for example, after obtaining a cross-sectional image (SEM image) by observing any 100 cross sections of the circuit connection adhesive film at a magnification of 5000 times through a scanning electron microscope (SEM), in any 20μm×15μm area in each cross-sectional image, the embedding rate of the conductive particles having the largest particle size L in the embedding direction and the conductive particles having a particle size L of 0.85 to 1.00 times that of the conductive particles is calculated, and their average value is set as the embedding rate of the conductive particles in each cross section. Next, the average value of the embedding rates of the conductive particles in the calculated 10 cross sections is calculated, and it is set as the embedding rate of the conductive particles in the circuit connection adhesive film (particle embedding rate).

[0096] The flow rate of each adhesive layer (the first adhesive layer 1 and the second adhesive layer 2) is the following flow rate, that is, the flow rate when the circuit connection adhesive film 10 is placed on a glass plate from the first adhesive layer 1 side, and temporary crimping is performed under the conditions of a crimping temperature of 70°C, a crimping pressure of 0.1 MPa, and a crimping time of 1.0 s, and then a glass plate is placed on the second adhesive layer 2 and formal crimping is performed under the conditions of a crimping temperature of 160°C, a crimping pressure of 2 MPa, and a crimping time of 5 seconds, and is defined by the following formula (2).

[0097] Flow rate [%] = S B / S A ×100···(2)

[0098] In formula (2), S A It represents the surface area of ​​the adhesive layer before temporary crimping, S B Indicates the area of ​​the adhesive layer after full crimping.

[0099] Specifically, the flow rate of each adhesive layer can be measured by the following procedures (I) to (IV).

[0100] (I) The adhesive film for circuit connection is punched out in the thickness direction with the substrates attached to both main surfaces of the adhesive film for circuit connection, thereby obtaining a disk-shaped adhesive film for evaluation having a radius r.

[0101] (II) After peeling off the substrate on the first adhesive layer side from the evaluation adhesive film, the evaluation adhesive film is placed on the first glass plate from the first adhesive layer side, and is hot-pressed from the second adhesive layer side under the conditions of a pressing temperature of 70°C, a pressing pressure of 0.1 MPa, and a pressing time of 1.0 second to obtain a temporary fixed body.

[0102] (III) After peeling off the substrate on the second adhesive layer side from the temporary fixed body, the second glass plate is placed on the second adhesive layer, and hot pressing is performed from the second adhesive layer side under the conditions of a pressing temperature of 160°C, a pressing pressure of 2 MPa, and a pressing time of 5 seconds to obtain a pressed body.

[0103] (IV) Calculating the bonding area S between the surface on the first adhesive layer side of the press-bonded structure and the first glass plate B1 (Unit: mm 2 ) and the bonding area S between the surface of the second adhesive layer side and the second glass plate B2 (Unit: mm 2 ), and the flow rate of the first adhesive layer and the flow rate of the second adhesive layer are calculated according to the following formula (2-1) and formula (2-2).

[0104] Flow rate of the first adhesive layer [%] = S B1 / (r 2 π)×100···(2-1)

[0105] Flow rate of the second adhesive layer [%] = S B2 / (r 2 π)×100···(2-2)

[0106] The particle embedding rate and flow ratio are within the above ranges, thereby suppressing the flow of the conductive particles during thermocompression bonding, and thus being able to fully secure the capture of the conductive particles. Furthermore, the particle embedding rate and flow ratio are within the above ranges, thereby suppressing the increase in connection resistance caused by the adhesive being interposed between the conductive particles and the connection portion. Therefore, the circuit connection adhesive film 10 is preferably suitable for use in bonding a first circuit component having a first electrode to a second circuit component having a second electrode and electrically connecting the first electrode and the second electrode to each other.

[0107] From the viewpoint of being able to further improve the capture rate of the conductive particles 3, the particle embedding rate of the first adhesive layer may be 38% or more, 45% or more, 52% or more, or 60% or more. From the viewpoint of being able to further reduce the connection resistance, the particle embedding rate of the first adhesive layer may be 85% or less, 75% or less, 65% or less, 55% or less, or 48% or less. From these viewpoints, the particle embedding rate of the first adhesive layer may be 38-85%, 45-75%, 52-75%, 60-75%, 30-65%, 30-55%, or 30-48%.

[0108] From the viewpoint of being able to further improve the capture rate of the conductive particles 3 and the viewpoint of being able to further reduce the connection resistance, the flow ratio may be 1.40 or more, 1.50 or more, 1.60 or more, or 1.70 or more. From the viewpoint of improving the connection reliability of the connection structure, the flow ratio may be 3.60 or less, 2.80 or less, 2.20 or less, or 1.70 or less. From these viewpoints, the flow ratio may be 1.40 to 3.60, 1.50 to 2.80, 1.60 to 2.80, 1.70 to 2.80, 1.20 to 2.20, or 1.20 to 1.70. The above-mentioned flow ratio is achieved, for example, by setting the first adhesive layer 1 as a cured product of a precursor layer containing an external stimulus curable composition.

[0109] From the viewpoint of further reducing the connection resistance, the flow rate of the first adhesive layer 1 may be 88% or more, or 92% or more, 95% or more, or 100% or more. From the viewpoint of further improving the capture rate of the conductive particles 3, the flow rate of the first adhesive layer 1 may be 110% or less, or 108% or less, or 106% or less. From these viewpoints, the flow rate of the first adhesive layer 1 may be 88-110%, or 92-110%, 95-108%, or 100-108%.

[0110] From the viewpoint of being able to further reduce the connection resistance, the flow rate of the second adhesive layer 2 may be 120% or more, or 150% or more, 160% or more, or 210% or more. From the viewpoint of being able to further improve the capture rate of the conductive particles 3, the flow rate of the second adhesive layer 2 may be 440% or less, or 400% or less, 350% or less, 300% or less, 250% or less, or 200% or less. From these viewpoints, the flow rate of the second adhesive layer 2 may be 120-440%, or 150-400%, 160-400%, 210-350%, 120-300%, 120-250%, or 120-200%.

[0111] The first adhesive layer 1 and the second adhesive layer 2 may have a thickness such that the conductive particles 3 are not exposed from the surface of the circuit-connecting adhesive film 10 (the surface of the first adhesive layer 1 opposite to the second adhesive layer 2 and the surface of the second adhesive layer 2 opposite to the first adhesive layer 1).

[0112] The thickness d1 of the first adhesive layer 1 ( Figure 2The distance indicated by d1 in the figure may be, for example, 0.5 μm or more, 1.0 μm or more, or 2.0 μm or more, or 50.0 μm or less, 40.0 μm or less, 30.0 μm or less, 20.0 μm or less, 10.0 μm or less, 5.0 μm or less, or 3.0 μm or less, or 0.5 to 50.0 μm, 1.0 to 40.0 μm, 2.0 to 30.0 μm, 1.0 to 20.0 μm, 1.0 to 10.0 μm, 1.0 to 5.0 μm, or 1.0 to 3.0 μm. If the thickness d1 of the first adhesive layer 1 is within the above range, it is easy to achieve both lower connection resistance and higher capture rate of conductive particles.

[0113] The thickness d2 of the second adhesive layer 2 ( Figure 2 The distance indicated by d2 in the figure can be, for example, 0.5 μm or more, 1.0 μm or more, 2.0 μm or more, or 3.0 μm or more, or 50.0 μm or less, 40.0 μm or less, 30.0 μm or less, 20.0 μm or less, 10.0 μm or less, or 0.5 to 50.0 μm, 1.0 to 40.0 μm, 2.0 to 30.0 μm, 3.0 to 20.0 μm, 3.0 to 10.0 μm, or 3.0 to 5.0 μm. If the thickness d2 of the second adhesive layer 2 is within the above range, the space between the electrodes can be fully filled to seal the electrodes, and better connection reliability can be easily obtained.

[0114] From the viewpoint of connection reliability of the connection structure, the thickness ratio of the thickness d2 of the second adhesive layer 2 to the thickness d1 of the first adhesive layer 1 may be 0.3 or more, or 1.0 or more, 2.0 or more, or 2.5 or more. From the viewpoint of capture rate of conductive particles, the thickness ratio of the thickness d2 of the second adhesive layer 2 to the thickness d1 of the first adhesive layer 1 may be 20.0 or less, or 15.0 or less, 12.0 or less, 10.0 or less, 6.0 or less, or 4.0 or less. From these viewpoints, the thickness ratio of the thickness d2 of the second adhesive layer 2 to the thickness d1 of the first adhesive layer 1 may be 0.3 to 20.0, or 1.0 to 15.0, 2.0 to 12.0, 2.0 to 10.0, 2.0 to 6.0, 2.0 to 4.0, or 2.5 to 10.0 from the viewpoint of connection reliability and low resistance of the connection structure.

[0115] The thickness of the circuit connection adhesive film 10 may be, for example, 2.0 μm or more, 3.0 μm or more, or 4.0 μm or more; 100.0 μm or less, 80.0 μm or less, 60.0 μm or less, 40.0 μm or less, 20.0 μm or less, or 10.0 μm or less; or 2.0 to 100.0 μm, 3.0 to 80.0 μm, 4.0 to 60.0 μm, 4.0 to 40.0 μm, 4.0 to 20.0 μm, or 4.0 to 10.0 μm.

[0116] The thickness d1 of the first adhesive layer 1, the thickness d2 of the second adhesive layer 2, and the thickness of the adhesive film 10 for circuit connection can be obtained, for example, by the following method: the adhesive film 10 for circuit connection is clamped by two glasses (thickness: about 1 mm), and a resin composition consisting of 100 g of bisphenol A epoxy resin (trade name: jER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (trade name: Epomount curing agent, manufactured by Refine Tec Ltd.) is injection molded, and then the cross-section is ground using a grinder and measured using a scanning electron microscope (SEM, trade name: SE-8020, manufactured by Hitachi Hi gh-Tech Corporation).

[0117] Next, the adhesive composition and the conductive particles 3 constituting the first adhesive layer 1 and the second adhesive layer 2 are described. Hereinafter, the adhesive composition constituting the first adhesive layer 1 is referred to as the "first adhesive composition", and the adhesive composition constituting the second adhesive layer 2 is referred to as the "second adhesive composition".

[0118] (First Adhesive Composition)

[0119] The first adhesive composition has thermosetting properties. That is, the first adhesive composition contains at least a thermosetting component.

[0120] The first adhesive composition is, for example, a cured product of an external stimulus curable composition formed by curing an external stimulus curable composition. The cured product of the external stimulus curable composition has thermosetting properties, so it can also be called a partially cured product. The external stimulus curable composition has the property of being cured by external stimuli such as heat, light, and stress. The external stimulus curable composition is, for example, a composition having thermosetting properties and photocuring properties. By photocuring a composition having thermosetting properties and photocuring properties, a cured product having thermosetting properties (cured product of the external stimulus curable composition) can be obtained. In the case where the external stimulus composition has thermosetting properties and photocuring properties, the external stimulus composition at least contains a thermosetting component and a photocuring component, and the first adhesive composition at least contains a cured product of the photocuring component and a thermosetting component.

[0121] [Thermosetting ingredients]

[0122] Thermosetting components are components that can flow during connection and are cured by heating. Thermosetting components include, for example, polymerizable compounds and thermal polymerization initiators. The polymerizable compounds may be free radical polymerizable compounds, cationic polymerizable compounds, or anionic polymerizable compounds. Similarly, the thermal polymerization initiator may be a thermal free radical polymerization initiator, a thermal cationic polymerization initiator, or a thermal anionic polymerization initiator. From the perspective of achieving a more excellent effect of reducing connection resistance, the polymerizable compound may be a cationic polymerizable compound, and the thermal polymerization initiator may be a thermal cationic polymerization initiator.

[0123] As a cationic polymerizable compound, from the viewpoint of further improving the effect of reducing the connection resistance and being more excellent in connection reliability, a compound having a cyclic ether group may be used. Among the compounds having a cyclic ether group, when at least one selected from the group consisting of alicyclic epoxy compounds and oxetane compounds is used, the effect of reducing the connection resistance also tends to be further improved. From the viewpoint of easily obtaining the desired melt viscosity, the cationic polymerizable compound may include both alicyclic epoxy compounds and oxetane compounds.

[0124] The alicyclic epoxy compound can be used without particular limitation as long as it is a compound having an alicyclic epoxy group (for example, an epoxycyclohexyl group). The alicyclic epoxy compound may be, for example, an epoxy compound having an epoxy equivalent of 100 to 300 g / eq. The epoxy equivalent is determined according to JIS K 7236.

[0125] Examples of commercially available alicyclic epoxy compounds include CELLOXIDE 8010 (trade name, bis-7-oxabicyclo[4.1.0]heptane, manufactured by Daicel Corporation) and EHPE 3150, EHPE 3150CE, CELLOXIDE 2021P, and CELLOXIDE 2081 (trade name, manufactured by Daicel Corporation).

[0126] As for the oxetane compound, as long as it is a compound having an oxetane group, it can be used without particular limitation. As a commercially available product of the oxetane compound, for example, ETERNACO LL OXBP (trade name, 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl, manufactured by UBE Corporation), OXSQ, OXT-121, OXT-221, OXT-101, OXT-212 (trade name, manufactured by Toagosei Company, Limited), etc. can be cited.

[0127] As a compound having a cyclic ether group, an epoxy compound other than an alicyclic epoxy compound can be used. Specifically, for example, an epoxy compound having an aromatic hydrocarbon group such as bisphenol A epoxy resin and bisphenol F epoxy resin (for example, the trade name "jER1010" manufactured by Mitsubishi Chemical Corporation, the trade name "TOPR-400" manufactured by NIPPON STEEL Chemical & Material Co., Ltd., etc.) can also be used. The epoxy equivalent of the epoxy compound having an aromatic hydrocarbon group can be 100 g / eq or more (for example, 100 to 3500 g / eq), or 150 g / eq or more (for example, 150 to 3500 g / eq). From the viewpoint of further improving the effect of reducing the connection resistance and better connection reliability, the epoxy compound having an aromatic hydrocarbon group can be used in combination with an alicyclic epoxy compound.

[0128] The thermal cationic polymerization initiator is, for example, a compound that generates an acid by heating and can start polymerization (thermal latent cationic initiator). The thermal cationic polymerization initiator can be a salt compound composed of a cation and an anion. As for the thermal cationic polymerization initiator, for example, BF4 - BR4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) PF6 - 、SbF6 - 、AsF6 - Onium salts such as sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, anilinium salts, pyridinium salts, etc. having anions such as these. These may be used alone or in combination of two or more.

[0129] From the viewpoint of rapid curing, the thermal cationic polymerization initiator may be, for example, a salt compound having an anion containing boron as a constituent element. As such a salt compound, for example, a salt compound having BF4 - or BR4 -(R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups.) The anion containing boron as a constituent element may be BR4 - , more specifically, may be tetrakis(pentafluorophenyl)borate.

[0130] From the viewpoint of storage stability, the thermal cationic polymerization initiator may be a salt compound having a cation represented by the following formula (I) or the following formula (II).

[0131]

[0132]

[0133] In formula (I), R 1 and R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing a substituted or unsubstituted aromatic hydrocarbon group, R 3 It represents an alkyl group having 1 to 6 carbon atoms.

[0134] Specific examples of the compound having a cation represented by the formula (I) include 1-naphthylmethyl-p-hydroxyphenylsulfonium hexafluoroantimonate (manufactured by SANSHIN CHEMICAL INDUSTRY CO., LTD., SI-60 main agent) and the like.

[0135] In formula (II), R 4 and R 5 Each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing a substituted or unsubstituted aromatic hydrocarbon group, R 6 and R 7 Each independently represents an alkyl group having 1 to 6 carbon atoms.

[0136] Specific examples of the compound having a cation represented by the formula (II) include YH-MS20 (trade name, manufactured by The Yokohama Rubber Co., Ltd.), CXC-1821 (trade name, manufactured by King Industries, Inc.), and the like.

[0137] From the viewpoint of ensuring the formability and curability of the adhesive film, the content of the thermal cationic polymerization initiator may be, for example, 0.1 to 25 parts by mass, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass based on 100 parts by mass of the cationically polymerizable compound.

[0138] From the viewpoint of ensuring the curability of the adhesive film, the content of the thermosetting component (e.g., the total content of the polymerizable compound and the thermal polymerization initiator) is based on the total mass of the first adhesive composition, for example, 3% by mass or more, 5% by mass or more, 10% by mass or more, or 15% by mass or more. From the viewpoint of ensuring the formability of the adhesive film, the content of the thermosetting component is based on the total mass of the adhesive composition, for example, 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less. From these viewpoints, the content of the thermosetting component is based on the total mass of the first adhesive composition, for example, 3 to 70% by mass, 5 to 60% by mass, 10 to 50% by mass, or 15 to 40% by mass. From the same viewpoint as above, the total content of the cationic polymerizable compound and the thermal cationic polymerization initiator can be within the above range.

[0139] [Photocurable component]

[0140] Photocurable components are components that are cured by light (active light rays). Photocurable components include, for example, polymerizable compounds and photopolymerization initiators. Polymerizable compounds may be free radical polymerizable compounds, cationic polymerizable compounds, or anionic polymerizable compounds. Similarly, photopolymerization initiators may be photoradical polymerization initiators, photocationic polymerization initiators, or photoanionic polymerization initiators. The type of photocurable component may be determined by considering the combination with the thermosetting component. For example, when the thermosetting component is a cationic polymerizable component, the photocurable component may be a free radical polymerizable component. That is, when the thermosetting component includes a cationic polymerizable compound and a thermal cationic polymerization initiator, the photocurable component may include a free radical polymerizable compound and a photoradical polymerization initiator.

[0141] Examples of the radical polymerizable compound include (meth)acrylate compounds, maleimide compounds, citraconimide compounds, nadic imide compounds, etc. From the perspective of easily obtaining the first adhesive layer with the above-mentioned fluidity, the photocurable component may include a (meth)acrylate compound, and from the perspective of easily obtaining the first adhesive layer with the above-mentioned fluidity, the photocurable component may include a multifunctional (meth)acrylate compound having two or more (meth)acryloyl groups.

[0142] Examples of the polyfunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-butylene glycol di(meth)acrylate, and 1,6-butylene glycol di(meth)acrylate. aliphatic (meth)acrylates such as 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerol di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate; ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate; di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, ethoxylated propoxylated fluorene di(meth)acrylate and other aromatic (meth)acrylates, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated Aliphatic (meth)acrylates such as pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexa(meth)acrylate; aromatic epoxy (meth)acrylates such as bisphenol type epoxy (meth)acrylate (for example, bisphenol A type epoxy (meth)acrylate), novolac type epoxy (meth)acrylate, and cresol novolac type epoxy (meth)acrylate, etc.

[0143] From the viewpoint of achieving both the effect of reducing connection resistance and suppressing particle flow, the content of the polyfunctional (meth)acrylate may be 40 to 100% by mass, 50 to 100% by mass, or 60 to 100% by mass based on the total mass of the polymerizable compound in the photocurable component.

[0144] From the viewpoint of easily obtaining the first adhesive layer with the above-mentioned fluidity, the photocurable component may include epoxy (meth) acrylate, and from the viewpoint of easily obtaining the first adhesive layer with the above-mentioned fluidity, the photocurable component may include aromatic epoxy (meth) acrylate. The content of epoxy (meth) acrylate is based on the total mass of the polymerizable compound in the photocurable component, and may be, for example, 40 to 100 mass %, 50 to 100 mass %, or 60 to 100 mass %.

[0145] From the viewpoint of easily obtaining the first adhesive layer with the above-mentioned fluidity, the photocurable component may contain a (meth)acrylate compound having a cross-linked structure such as a tricyclodecane structure and a norbornane structure and / or an aromatic structure. The content of the (meth)acrylate compound having a cross-linked structure such as a tricyclodecane structure and a norbornane structure and / or an aromatic structure may be, for example, 40 to 100% by mass, 50 to 100% by mass, or 60 to 100% by mass, based on the total mass of the polymerizable compound in the photocurable component.

[0146] The photoradical polymerization initiator is a photopolymerization initiator that generates free radicals by irradiating light (e.g., ultraviolet light) with a wavelength in the range of 150 to 750 nm. The photoradical polymerization initiator may be a compound having structures such as an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyl dimethyl ketal structure, and an α-hydroxyalkylphenone structure. From the viewpoint of easily obtaining the desired melt viscosity and the viewpoint of having a better effect by reducing the connection resistance, the photoradical polymerization initiator may be a compound having at least one structure selected from the group consisting of an oxime ester structure, an α-aminoalkylphenone structure, and an acylphosphine oxide structure.

[0147] Specific examples of the compound having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(o-acetyloxime), and the like.

[0148] Specific examples of the compound having an α-aminoalkylphenone structure include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one and 2-benzyl-2-dimethylamino-1-morpholinophenyl)-butanone-1-one.

[0149] Specific examples of the compound having an acylphosphine oxide structure include bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, bis(2,4,6,-trimethylbenzoyl)-phenylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0150] From the viewpoint of easily obtaining the first adhesive layer having the above-mentioned fluidity, the content of the photoradical polymerization initiator may be, for example, 0.1 to 10 parts by mass, 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass based on 100 parts by mass of the radical polymerizable compound.

[0151] From the viewpoint of easily obtaining the first adhesive layer of the above-mentioned flow rate, the content of the photocurable component (for example, the total content of the polymerizable compound and the photopolymerization initiator) is based on the total mass of the first adhesive composition, for example, 3% by mass or more, 5% by mass or more, or 10% by mass or more. From the viewpoint of easily obtaining the desired melt viscosity and the viewpoint of having a better effect of reducing the connection resistance, the content of the photocurable component is based on the total mass of the adhesive composition, for example, 50% by mass or less, 40% by mass or less, or 30% by mass or less. From these viewpoints, the content of the thermosetting component is based on the total mass of the first adhesive composition, for example, 3 to 50% by mass, 5 to 40% by mass, or 10 to 30% by mass. From the same viewpoint as above, the total content of the radical polymerizable compound and the photoradical polymerization initiator can be within the above range.

[0152] [Other ingredients]

[0153] The first adhesive composition may further contain, for example, a thermoplastic resin, a filler, a coupling agent, and the like.

[0154] Thermoplastic resins contribute to improving the film forming properties of the adhesive film. As thermoplastic resins, for example, phenoxy resins, polyester resins, polyamide resins, polyurethane resins, polyester polyurethane resins, acrylic rubbers, epoxy resins (solid at 25°C), etc. can be cited. As the above-mentioned phenoxy resins, for example, fluorene-type phenoxy resins (epoxy resins containing fluorene skeletons), bisphenol A / bisphenol F copolymerization phenoxy resins (phenoxy resins containing bisphenol A skeletons and bisphenol F skeletons), etc. can be cited. Among these, when using bisphenol A / bisphenol F copolymerization phenoxy resins, there is a tendency to easily take into account the properties (such as film forming properties) derived from thermoplastic resins and the curing properties of the connecting portion in the connecting structure. They can be used alone or in combination.

[0155] From the viewpoint of resin expulsion during connection (installation), the weight average molecular weight (Mw) of the thermoplastic resin may be, for example, 5000 to 200000, 10000 to 100000, 20000 to 80000, or 40000 to 60000. Mw is measured by gel permeation chromatography (GPC) and is converted using a calibration curve based on standard polystyrene.

[0156] The content of the thermoplastic resin may be, for example, 1% by mass or more, 5% by mass or more, 10% by mass or more, or 20% by mass or more, and may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, and may be 1 to 70% by mass, 5 to 60% by mass, 10 to 50% by mass, or 20 to 40% by mass, based on the total mass of the first adhesive composition.

[0157] As the filling material, for example, non-conductive fillers (such as non-conductive particles) can be mentioned. The filling material can be any of an inorganic filler and an organic filler. As the inorganic filler, for example, metal oxide particles such as silica particles, alumina particles, silica aluminum oxide particles, titanium dioxide particles, zirconium dioxide particles; inorganic particles such as metal nitride particles can be mentioned. As the organic filler, for example, organic particles such as silicone particles, methacrylate-butadiene-styrene particles, acrylic-silicone particles, polyamide particles, polyimide particles can be mentioned. From the viewpoint of the connection reliability of the connecting structure, the filling material can be silica particles, or silica particles surface-treated with silane compounds such as phenyltrimethoxysilane and octylsilane.

[0158] The average particle size of the filler may be 0.25 to 20 μm. Here, the average particle size of the filler is a value measured by a flow particle image analyzer (for example, FPIA-3000S from Sysmex Corporation).

[0159] The content of the filler may be, for example, 0.1 to 10% by mass based on the total mass of the first adhesive composition.

[0160] As the coupling agent, for example, silane coupling agents having organic functional groups such as (meth)acryloyl, mercapto, amino, imidazole, epoxy, etc. (γ-glycidyloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.), silane compounds such as tetraalkoxysilane, tetraalkoxy titanate derivatives, polydialkyl titanate derivatives, etc. can be cited. Among these, when a silane coupling agent having an organic functional group is used, the adhesion of the first adhesive composition tends to be further improved. The content of the coupling agent can be, for example, 0.1 to 10% by mass based on the total mass of the first adhesive composition.

[0161] As other components, the first adhesive composition may further include a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. The content of these components may be, for example, 0.1 to 10% by mass based on the total mass of the first adhesive composition.

[0162] (Second Adhesive Composition)

[0163] The second adhesive composition has thermosetting properties. That is, the second adhesive composition contains at least a thermosetting component. As the thermosetting component, the thermosetting component exemplified as the above-mentioned thermosetting component contained in the first adhesive composition can be used.

[0164] From the viewpoint of achieving a better effect of reducing connection resistance, the thermosetting component may include a cationically polymerizable compound and a thermal cationic polymerization initiator. The content of the thermal cationic polymerization initiator in the second adhesive composition may be the same as the content of the thermal cationic polymerization initiator in the first adhesive composition.

[0165] From the viewpoint of easily obtaining the desired melt viscosity, the cationic polymerizable compound may include both alicyclic epoxy compounds and oxetane compounds. From the viewpoint of further improving the effect of reducing the connection resistance and having a better connection reliability, alicyclic epoxy compounds and epoxy compounds having aromatic hydrocarbon groups may be used in combination. Furthermore, from the viewpoint of connection reliability of the connection structure, rubber-modified alicyclic epoxy compounds may be used.

[0166] From the viewpoint of ensuring the curability of the adhesive film, the content of the thermosetting component (e.g., the total content of the polymerizable compound and the thermal polymerization initiator) is based on the total mass of the second adhesive composition, for example, 3% by mass or more, 5% by mass or more, 10% by mass or more, or 15% by mass or more. From the viewpoint of ensuring the formability of the adhesive film, the content of the thermosetting component is based on the total mass of the adhesive composition, for example, 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less. From these viewpoints, the content of the thermosetting component is based on the total mass of the first adhesive composition, for example, 3 to 70% by mass, 5 to 60% by mass, 10 to 50% by mass, or 15 to 40% by mass. From the same viewpoint as above, the total content of the cationic polymerizable compound and the thermal cationic polymerization initiator can be within the above range.

[0167] The second adhesive composition may further contain components such as a thermoplastic resin, a filler, and a coupling agent, similarly to the first adhesive composition. As these components, the components exemplified as the components that can be contained in the first adhesive composition can be used.

[0168] When a fluorene-type phenoxy resin is also used in the thermoplastic resin, there is a tendency to easily take into account both film-forming properties and connection reliability of the connection structure. The content of the thermoplastic resin is based on the total mass of the second adhesive composition, for example, 1% by mass or more, 5% by mass or more, 10% by mass or more, or 20% by mass or more, 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, and can be 1-70% by mass, 5-60% by mass, 10-50% by mass, or 20-40% by mass.

[0169] From the perspective of connection reliability of the connection structure, the filler may be silica particles or silica particles surface-treated with silane compounds such as phenyltrimethoxysilane and octylsilane. The content of the filler may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive composition.

[0170] When a silane coupling agent having an organic functional group is also used as the coupling agent, the adhesiveness of the second adhesive composition tends to be further improved. The content of the coupling agent may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive composition.

[0171] The second adhesive composition may further include a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. The content of these components may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive composition.

[0172] The second adhesive composition may contain ε-caprolactam as a thermosetting reaction rate regulator. The content of ε-caprolactam may be, for example, 0.005 to 0.1% by mass based on the total mass of the second adhesive composition.

[0173] The second adhesive composition may contain tributyl borate as an additive. Tributyl borate can function as a viscosity modifier, etc. The content of tributyl borate may be, for example, 0.1 to 2.0% by mass based on the total mass of the second adhesive composition.

[0174] (Conductive particles)

[0175] Conductive particles 3 are particles with conductivity. As conductive particles 3, metal particles composed of metals such as Au, Ag, Ni, Cu, solder, conductive carbon particles composed of conductive carbon, etc. can be used. Conductive particles 3 can be coated conductive particles having a core containing non-conductive glass, ceramics, plastics (polystyrene, etc.) and a coating layer containing the above-mentioned metal or conductive carbon and coating the core. Among these, in the case of using coated conductive particles having a core containing metal particles or plastics formed by hot-melt metal and a coating layer containing metal or conductive carbon and coating the core, it is easy to deform the first adhesive layer by heating or pressurizing. Therefore, when the electrodes are electrically connected to each other, the contact area between the electrodes and the conductive particles can be increased, and the conductivity between the electrodes can be further improved.

[0176] The conductive particles 3 may be the above-mentioned metal particles, conductive carbon particles, or insulating coated conductive particles having an insulating layer that covers the conductive particles and an insulating material such as a resin and covers the surface of the particles. If the conductive particles 3 are insulating coated conductive particles, even when the conductive particle content is high, since the surface of the particles is coated with resin, short circuits caused by contact between the conductive particles can be suppressed, and the insulation between adjacent electrode circuits can be improved.

[0177] From the viewpoint of the availability of raw materials and the formation of a connection structure required by the market, the average particle size of the conductive particles 3 can be 1.0 to 50.0 μm. Furthermore, from the viewpoint of the connection reliability of the structure, the CV value of the particle size of the conductive particles 3 can be 25% or less. From these viewpoints, the conductive particles 3 can be particles having an average particle size of 1.0 to 50.0 μm and a CV value of the particle size of 25% or less. In this specification, the average particle size of the conductive particles is the average value of the particle size of the conductive particles in the embedding direction measured by the above method, and the CV value of the particle size of the conductive particles is the CV value of the particle size of the conductive particles in the embedding direction measured by the above method. The CV value of the particle size is a value calculated by multiplying the value obtained by dividing the standard deviation of the particle size by the average particle size by 100, and is a parameter indicating the degree of deviation of the particle size. A small CV value of the particle size indicates a small deviation of the particle size. The average particle size of the conductive particles and the CV value of the particle size of the conductive particles can be measured by observing a longitudinal section (cross section in the thickness direction) of the circuit connecting adhesive film using a scanning electron microscope (SEM) in the same manner as the method for measuring the particle embedding rate.

[0178] From the viewpoint of reducing resistance, the average particle size of the conductive particles 3 may be 2.0 μm or more or 4.0 μm or more. From the viewpoint of connection reliability of the connection structure, the average particle size of the conductive particles 3 may be 40.0 μm or less or 25.0 μm or less. From these viewpoints, the average particle size of the conductive particles 3 may be 2.0 to 40.0 μm or 4.0 to 25.0 μm.

[0179] From the viewpoint of connection reliability of the connection structure, the CV value of the particle size of the conductive particles 3 may be 20% or less or 15% or less. The lower limit of the CV value of the particle size of the conductive particles 3 is preferably as small as possible, and may be 0%, 1%, or 3%. The CV value of the particle size of the conductive particles 3 may be, for example, 0 to 25%, 1 to 20%, or 3 to 15%.

[0180] From the viewpoint of preventing the conductive particles 3 from being exposed from the surface of the adhesive film 10 for circuit connection, the ratio of the thickness of the adhesive film 10 for circuit connection to the average particle size of the conductive particles 3 may be 1.1 or more, or 1.5 or more, 2.0 or more, or 2.5 or more. From the viewpoint of reducing the resistance, the ratio of the thickness of the adhesive film 10 for circuit connection to the average particle size of the conductive particles 3 may be 10.0 or less, or 8.0 or less, 5.0 or less, or 3.0 or less. From these viewpoints, the ratio of the thickness of the adhesive film 10 for circuit connection to the average particle size of the conductive particles 3 may be 1.1 to 10.0, or 1.5 to 8.0, 2.0 to 5.0, 2.5 to 5.0, or 1.5 to 3.0.

[0181] From the viewpoint of easily obtaining a stable connection resistance, the particle density of the conductive particles 3 may be 5000 particles / mm 2 Above, 10000 pieces / mm 2 Above or 20000 pcs / mm 2 From the viewpoint of improving the insulation between adjacent electrodes, the particle density of the conductive particles 3 may be 50,000 particles / mm 2 Below, 40000 pieces / mm 2 Below or 30000 pcs / mm 2 From these viewpoints, the particle density of the conductive particles 3 may be 5,000 to 50,000 particles / mm 2 10000~40000pcs / mm 2 or 20000~30000pcs / mm 2 .

[0182] From the viewpoint of being able to further improve the conductivity, the content of the conductive particles 3 can be, for example, 40% by mass or more, 50% by mass or more, or 60% by mass or more, based on the total mass of the adhesive film 10 for circuit connection. From the viewpoint of easily suppressing short circuits, the content of the conductive particles 3 can be, for example, 80% by mass or less, 75% by mass or less, or 70% by mass or less, based on the total mass of the adhesive film 10 for circuit connection. From these viewpoints, the content of the conductive particles 3 can be, for example, 40 to 80% by mass, 50 to 75% by mass, or 60 to 70% by mass, based on the total mass of the adhesive film 10 for circuit connection.

[0183] An embodiment of the adhesive film for circuit connection is described above, but the adhesive film for circuit connection is not limited to the above embodiment. For example, when the adhesive film for circuit connection is viewed from above, the plurality of conductive particles in the adhesive film for circuit connection may not be arranged in a predetermined pattern. In addition, the adhesive film for circuit connection may further include other adhesive layers other than the first adhesive layer and the second adhesive layer.

[0184] <Method for producing adhesive film for circuit connection>

[0185] The method for manufacturing an adhesive film for circuit connection includes: step (I), preparing a first adhesive film having a first adhesive layer and conductive particles partially embedded in one side of the first adhesive layer; and step (II), providing a second adhesive layer on one side of the first adhesive layer, wherein step (I) includes: a curing step of forming the first adhesive layer by curing the precursor layer by external stimulation in a state in which the conductive particles are partially embedded in one side of a precursor layer containing an external stimulation curable composition.

[0186] Step (I) may further include a transfer step, wherein the precursor layer is provided on the surface of a substrate having a plurality of conductive particles disposed thereon, and the conductive particles are transferred from the substrate to the precursor layer. By implementing the transfer step, adjacent conductive particles can be easily embedded in the precursor layer in a state of being separated from each other.

[0187] Step (I) may further include a heating step, wherein the layer comprising the external stimulus curable composition is heated at 50 to 70° C. for 3 to 60 minutes before the transfer step. By implementing the heating step, the embedding rate of the conductive particles in the precursor layer in the transfer step can be adjusted, thereby easily obtaining an adhesive film for circuit connection having a desired particle embedding rate. In the case where the precursor layer has sufficient hardness to obtain the desired particle embedding rate, the heating step may not be implemented.

[0188] Step (I) may further include a pressurizing step, in which pressure is applied to the surface of the precursor layer to which the conductive particles are transferred after the transfer step. By implementing the pressurizing step, the conductive particles can be further embedded in the precursor layer, thereby increasing the particle embedding rate. In the case where a sufficient particle embedding rate is obtained in the transfer step, the pressurizing step may not be implemented.

[0189] Below, reference Figures 4 to 7 , the manufacturing method of the circuit connection adhesive film 10 of the above embodiment is taken as an example to describe the manufacturing method of the circuit connection adhesive film. In addition, the description that overlaps with the description of the circuit connection adhesive film 10 of the above embodiment, such as the details of the first adhesive layer, the conductive particles, the second adhesive layer, the external stimulus curable composition, etc., will be omitted.

[0190] Figure 4 It is a schematic diagram which shows the transfer process in process (I). Figure 5 This is a schematic diagram showing the pressurizing step in step (I). Figure 6 This is a schematic diagram showing the curing step in step (I). Figure 7 It is a schematic diagram which shows the process (II).

[0191] (Step (I))

[0192] [Preparation of substrate]

[0193] In step (I), first, a film including a precursor layer containing an external stimulus curable composition and a substrate having a plurality of conductive particles arranged on the surface are prepared.

[0194] As a film having a precursor layer containing an external stimulus curable composition, for example, Figure 4The laminated film 12 shown in (a) of FIG. 1 includes a first support 21 and a precursor layer 11 provided on the first support 21 .

[0195] The first support 21 may be a plastic film or a metal foil. As the first support 21, for example, a substrate (e.g., a film) made of stretched polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. may be used.

[0196] The precursor layer 11 can be formed by applying an external stimulus curable composition or a solution thereof (varnish) on the first support 21, and optionally heating and drying to obtain a layer (a layer containing an external stimulus curable composition). Regarding the varnish, it is prepared by mixing the constituent components of the external stimulus curable composition in an organic solvent. Regarding the coating, a blade coater, a roller coater, an applicator, a comma coater, a die coater, etc. can be used. The heating conditions for volatilizing the organic solvent from the varnish applied to the substrate can be set according to the type of organic solvent used, etc., but in this embodiment, from the perspective of adjusting the embedding rate of the conductive particles in the precursor layer in the transfer process, it can be dried for a longer time than usual. The heating conditions can be, for example, 50 to 70°C and 3 to 60 minutes. However, the heating conditions can be adjusted according to the melt viscosity of the target precursor layer 11.

[0197] The minimum melt viscosity of the precursor layer 11 can be 30 to 10000 Pa·s, or 50 to 5000 Pa·s. The minimum melt viscosity of the precursor layer can be obtained, for example, as follows: a laminator (Leon13DX (LAMICORPORATION INC.)) is used to make the precursor layer reach a thickness of 300μm to 500μm, and after stacking multiple layers, the obtained stacked samples are subjected to viscoelasticity measurement using ARES-G2 (TA Instruments.). The stacking conditions of the precursor layer can be carried out, for example, at 50°C, a paper feed speed of 1m / min, and a device setting of S8. The viscoelasticity measurement is carried out, for example, within a measurement temperature range of 0°C to 200°C. The lowest value of the measured melt viscosity (Pa·s) is set to the minimum melt viscosity. The precursor layer preferably shows a complex viscosity of 1000 to 10000 Pa·s at any temperature in the range of 20°C to 80°C. More preferably, the complex viscosity is about 2000 Pa·s (eg, 1500 to 3000 Pa·s) at any temperature within the range of 40°C to 70°C.

[0198] About the organic solvent used in the preparation of varnish, as long as there is the characteristic that can roughly evenly dissolve or disperse the constituent of external stimulus curable composition, then it is not particularly limited.As this organic solvent, for example, toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate etc. can be enumerated.Their organic solvent can be used alone or in combination with more than 2 kinds.Mixing during preparation varnish, for example, can use stirrer, dispersion machine, three rollers, ball mill, bead mill, homogeneous dispersion machine etc. to carry out.

[0199] As a substrate, for example, Figure 4 The substrate 22 shown in (a) has a plurality of recesses on the surface of the substrate 22, in which conductive particles are arranged. The plurality of recesses are regularly arranged, for example, in a predetermined pattern (for example, a pattern corresponding to an electrode pattern of a circuit component). When the recesses are arranged in a predetermined pattern, the conductive particles 3 are transferred to the first adhesive layer in the predetermined pattern. Therefore, a predetermined pattern (such as Figure 1 An adhesive film 10 for circuit connection in which conductive particles 3 are regularly arranged (in a pattern shown in FIG. 1 ). The shape and size of the recessed portion of the substrate 22 can be set from the viewpoints of the shape and size of the conductive particles, the particle embedding rate in the first adhesive layer, etc. As the material constituting the substrate 22, for example, inorganic materials such as silicon, various ceramics, glass, stainless steel and other metals, and organic materials such as various resins can be used. The method of arranging (accommodating) the conductive particles 3 in the recessed portion of the substrate 22 is not particularly limited. For example, the conductive particles 3 are arranged on the surface of the substrate 22, and the surface of the substrate 22 is wiped with a scraper or a micro-adhesive roller, thereby removing excess conductive particles 3 while arranging the conductive particles 3 in the recessed portion. As a method for removing excess solder particles, a method of spraying compressed air or wiping the surface of the substrate 22 with a non-woven fabric or a fiber bundle can also be cited. In addition, by forming the conductive particles 3 in the recessed portion of the substrate 22, the conductive particles 3 can be arranged in the recessed portion. Although not shown in the drawings, a substrate having support portions (needles or the like) capable of fixing conductive particles on the surface may be used instead of the substrate 22 .

[0200] [Transfer process]

[0201] Next, by providing the above-mentioned precursor layer 11 on the surface of the conductive particles 3 provided with the substrate 22, the conductive particles 3 are transferred from the substrate 22 to the precursor layer 11 (refer to Figure 4 Specifically, first, the surface of the substrate 22 having the recessed portion (the surface of the substrate 22) is placed opposite to the surface of the precursor layer 11 of the laminate film 12 (the surface of the precursor layer 11 opposite to the first support 21), so that the substrate 22 and the precursor layer 11 are close to each other (refer to Figure 4Next, the laminated film 12 and the substrate 22 are bonded together so that the precursor layer 11 is in contact with the surface (surface with the recessed portion) of the substrate 22, and the conductive particles 3 are transferred to the precursor layer 11 (refer to Figure 4 (b). Thus, we can obtain Figure 4 The laminated film 13 with first particles shown in (c) . The laminated film 13 with first particles includes a first support 21 , a precursor layer 11 , and conductive particles 3 partially embedded in the precursor layer 11 .

[0202] Examples of methods for laminating the laminate film 12 and the substrate 22 include heat pressing, roll lamination, vacuum lamination, etc. Lamination can be performed at a temperature of 0 to 80° C. The temperature during transfer can be the lowest temperature at which the particle transfer rate to the precursor layer 11 reaches 98% or more.

[0203] Although not shown in the drawings, in the transfer step, the precursor layer 11 may be formed by directly applying the external stimulus curable composition or a solution (varnish) thereof to the base 22 .

[0204] [Pressing process]

[0205] Next, pressure is applied to the surface of the precursor layer 11 to which the conductive particles 3 are transferred. Figure 5 As shown in (a), after the protective film 23 is attached to the surface of the precursor layer 11 to which the conductive particles 3 are transferred, pressure is applied to the laminated film 13 with the first particles from the first support 21 side and the protective film 23 side ( Figure 5 Thus, the conductive particles 3 are further embedded in the precursor layer, and a Figure 5 The laminated film 14 with the second particles shown in (b) .

[0206] As the protective film 23 , for example, a release film having a surface subjected to a release treatment can be used. Depending on the type of the precursor layer 11 , the protective film 23 may not be used.

[0207] As a method of applying pressure, for example, lamination, roll lamination, vacuum lamination and the like can be cited. The pressure can be 0.1 to 10 MPa. The pressing time can be 0.5 to 20 seconds. In the pressing step, heating can be performed while pressing. The temperature during pressing can be set to 20 to 70° C., for example.

[0208] [Curing process]

[0209] Next, an external stimulus is applied to the precursor layer 11 containing the external stimulus curable composition to cure the precursor layer. Figure 6As shown in (a), when the external stimulus curable composition is a composition having thermosetting and photocuring properties, the precursor layer 11 is cured by irradiating light (active light) 24 to the precursor layer 11. Thus, it is possible to obtain Figure 6 The first adhesive film 15 shown in (b) of FIG. 1 includes a first support 21 , a first adhesive layer 1 , and conductive particles 3 partially embedded in one surface side of the first adhesive layer 1 (the side opposite to the first support 21 ).

[0210] In the irradiation of light, irradiation light (e.g., ultraviolet light) in the wavelength range of 150 to 750 nm can be used. Regarding the irradiation of light, for example, a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, etc. can be used. The irradiation amount of light is not particularly limited, and can be 100 mJ / cm in terms of the cumulative light amount of light with a wavelength of 350 nm. 2 Above, can be 200mJ / cm 2 Above, can be 300mJ / cm 2 The amount of light irradiation is measured as the cumulative amount of light with a wavelength of 365 nm, which can be 10000 mJ / cm 2 Below, can be 5000mJ / cm 2 Below, can be 3000mJ / cm 2 the following.

[0211] exist Figure 6 The laminated film 14 with the second particles is used, but when the pressurization step is not performed, the laminated film 13 with the first particles can be used instead of the laminated film 14 with the second particles. In addition, in the curing step, heat treatment can be performed instead of light irradiation or in addition to light irradiation.

[0212] (Step (II))

[0213] In step (II), first, a film having a second adhesive layer 2 is prepared. As the film having the second adhesive layer 2, the following can be used: Figure 7 The second adhesive film 16 shown in (a) of FIG. 1 includes a second support 25 and a second adhesive layer 2 provided on the second support 25 .

[0214] The substrate exemplified as the first support 21 can be used as the second support 25. The second adhesive layer 2 can be formed in the same manner as the precursor layer 11 except that the second adhesive composition is used instead of the external stimulus curable composition.

[0215] Next, the second adhesive film 16 is attached to the first adhesive layer 1 side (the first adhesive layer 1 opposite to the support 21) of the first adhesive film 15 prepared in step (I) from the second adhesive layer 2 side, and the second adhesive layer 2 is stacked on the first adhesive layer 1 (refer to Figure 7 ). Thus, we can obtain Figure 7 The adhesive film 17 for circuit connection with a support shown in (b) of FIG. The adhesive film 17 for circuit connection with a support includes a first support 21 , the adhesive film 10 for circuit connection, and a second support 25 .

[0216] Examples of a method for bonding the first adhesive film 15 and the second adhesive film 16 include heat pressing, roll lamination, vacuum lamination, etc. The lamination can be performed at a temperature of 0 to 80°C, for example.

[0217] In step (II), the second adhesive layer 2 can be provided on the first adhesive layer 1 by directly applying the second adhesive composition or a solution thereof (varnish) to the first adhesive layer 1 in the same manner as the method of forming the second adhesive layer on the second support 25 .

[0218] <Connection structure and method for manufacturing the same>

[0219] The connection structure comprises: a first circuit component having a first electrode; a second circuit component having a second electrode electrically connected to the first electrode; and a connection portion electrically connecting the first electrode and the second electrode to each other via conductive particles and bonding the first circuit component to the second circuit component. The connection portion comprises a cured product of an adhesive film for circuit connection.

[0220] The manufacturing method of a connection structure includes the following steps: disposing a circuit connection adhesive film between a surface of a first circuit component having a first electrode and provided with the first electrode, and a surface of a second circuit component having a second electrode and provided with the second electrode; and heating a stack including the first circuit component, the circuit connection adhesive film and the second circuit component while being pressed in a thickness direction of the stack, thereby electrically connecting the first electrode and the second electrode to each other via conductive particles and bonding the first circuit component to the second circuit component.

[0221] Below, reference Figure 8 and Fig. 9 , taking a connection structure (circuit connection structure) and a method for producing the same using the circuit connection adhesive film 10 as a connection material as an example, the connection structure and the method for producing the same are described.

[0222] Figure 8 Schematic cross-sectional view showing one embodiment of a connection structure. Figure 8As shown, the connection structure 100 comprises: a first circuit component 33, having a first circuit substrate 31 and a first electrode 32 formed on a main surface 31a of the first circuit substrate 31; a second circuit component 36, having a second circuit substrate 34 and a second electrode 35 formed on a main surface 34a of the second circuit substrate 34; and a connecting portion 40, which electrically connects the first electrode 32 and the second electrode 35 to each other via conductive particles 43 and bonds the first circuit component 33 and the second circuit component 36.

[0223] The first circuit component 33 and the second circuit component 36 may be the same or different from each other. The first circuit component 33 and the second circuit component 36 may be a glass substrate or a plastic substrate on which circuit electrodes are formed; a printed circuit board; a ceramic circuit board; a flexible circuit board; an IC chip such as a driver IC, etc. The first circuit substrate 31 and the second circuit substrate 34 may be formed of inorganic materials such as semiconductors, glass, and ceramics, organic materials such as polyimide and polycarbonate, and composites such as glass / epoxy. The first circuit substrate 31 may be a plastic substrate. The first circuit component 33 may be, for example, a plastic substrate on which circuit electrodes are formed (a plastic substrate made of organic materials such as polyimide, polycarbonate, polyethylene terephthalate, and cycloolefin polymer), and the second circuit component 36 may be, for example, an IC chip such as a driver IC. The plastic substrate on which electrodes are formed may be a plastic substrate on which a display area is formed by regularly arranging pixel driving circuits such as organic TFTs or a plurality of organic EL elements R, G, and B in a matrix shape on the plastic substrate.

[0224] The first electrode 32 and the second electrode 35 may be electrodes including metals such as gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, and oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO). The first electrode 32 and the second electrode 35 may be electrodes formed by stacking two or more of these metals, oxides, and the like. The electrode formed by stacking two or more of these metals, oxides, and the like may have more than two layers or more than three layers. The first electrode 32 and the second electrode 35 may be circuit electrodes or bump electrodes. Figure 8 In the embodiment, the first electrode 32 is a circuit electrode, and the second electrode 35 is a bump electrode.

[0225] The total value of the height of the first electrode 32 and the height of the second electrode 35 may be smaller than the average particle size of the conductive particles 3 in the circuit connection adhesive film used to form the connection portion 40. The total value may be, for example, 30 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, 5 μm or less, less than 4 μm, less than 3 μm, less than 2 μm, or less than 1 μm. The height of the first electrode 32 (for example, the height of the circuit electrode) may be, for example, 0.05 to 5.0 μm, 0.1 to 4.0 μm, or 0.5 to 3.0 μm. The height of the second electrode 35 (for example, the height of the bump electrode) may be, for example, 0.5 to 25.0 μm, 2.0 to 15.0 μm, or 5.0 to 10.0 μm.

[0226] The connection portion 40 is a cured product of the circuit-connecting adhesive film 10. The connection portion 40 includes, for example, a first region 41 located on the first circuit component 33 side in the direction in which the first circuit component 33 and the second circuit component 36 are opposed to each other and includes a cured product of the first adhesive layer 1; a second region 42 located on the second circuit component 36 side in the direction in which the first circuit component 33 and the second circuit component 36 are opposed to each other and includes a cured product of the second adhesive layer 2; conductive particles 43 interposed between the first electrode 32 and the second electrode 35 to electrically connect the first electrode 32 and the second electrode 35 to each other; and conductive particles 3 located between adjacent electrodes. The connection portion 40 may not have two distinct regions between the first region 41 and the second region 42, and may include, for example, a region cured in a state where the first adhesive layer 1 and the second adhesive layer 2 are mixed.

[0227] As examples of the connection structure, there can be cited a color display formed by connecting a plastic substrate on which micro LED elements (light-emitting elements) are regularly arranged with a driving circuit element as a driver for image display, and a touch panel formed by connecting a plastic substrate on which micro LED elements are regularly arranged with a position input element such as a touch pad. The connection structure can be an organic EL display device in which the LED element is an organic EL element. The connection structure can also be applied to various monitors such as smartphones, tablet computers, televisions, navigation systems of vehicles, wearable terminals, furniture, home appliances, daily necessities, etc.

[0228] Fig. 9 This is a schematic cross-sectional view showing an embodiment of a method for producing the connection structure 100 . Fig. 9 (a) and Fig. 9 (b) is a schematic cross-sectional view showing each process. Fig. 9As shown, the manufacturing method of the connection structure 100 includes the following steps: arranging the above-mentioned circuit connection adhesive film 10 between the surface of the first circuit component 33 provided with the first electrode 32 and the surface of the second circuit component 36 provided with the second electrode 35; and heating the stack including the first circuit component 33, the circuit connection adhesive film 10 and the second circuit component 36 while being pressed in the thickness direction of the stack, thereby electrically connecting the first electrode 32 and the second electrode 35 to each other via the conductive particles 43, and bonding the first circuit component 33 and the second circuit component 36.

[0229] Specifically, first, a first circuit component 33 including a first circuit substrate 31 and a first electrode 32 formed on a main surface 31a of the first circuit substrate 31 and a second circuit component 36 including a second circuit substrate 34 and a second electrode 35 formed on a main surface 34a of the second circuit substrate 34 are prepared.

[0230] Next, the first circuit member 33 and the second circuit member 36 are arranged so that the first electrode 32 and the second electrode 35 face each other, and the circuit connection adhesive film 10 is arranged between the first circuit member 33 and the second circuit member 36. Fig. 9 As shown in (a), the circuit connection adhesive film 10 is laminated on the first circuit component 33 so that the first adhesive layer 1 side is opposed to the main surface 31a of the first circuit substrate 31. Then, the second circuit component 36 is arranged on the first circuit component 33 laminated with the circuit connection adhesive film 10 in a manner that the first electrode 32 on the first circuit substrate 31 and the second electrode 35 on the second circuit substrate 34 are opposed to each other.

[0231] And, if Fig. 9 As shown in (b), the first circuit component 33 and the second circuit component 36 are heat-pressed to each other by heating the laminated body formed by sequentially laminating the first circuit component 33, the circuit connection adhesive film 10, and the second circuit component 36 while pressing the laminated body in the thickness direction. Fig. 9 As shown by the arrows in (b), the uncured thermosetting components contained in the first adhesive layer 1 and the second adhesive layer 2 flow in a manner that fills the gaps between the electrodes adjacent to each other (the gaps between the first electrodes 32 and the gaps between the second electrodes 35), and are cured by the above-mentioned heating. As a result, the first electrode 32 and the second electrode 35 are electrically connected to each other via the conductive particles 43, and the first circuit component 33 and the second circuit component 36 are bonded to each other, so that Figure 8 The connection structure 100 is shown.

[0232] The temperature and time during thermocompression bonding may be any temperature at which the circuit-connecting adhesive film 10 is sufficiently cured and the first circuit member 33 and the second circuit member 36 can be bonded. The thermocompression bonding temperature may be 150 to 200° C. The thermocompression bonding time may be 4 to 7 seconds.

[0233] Example

[0234] Hereinafter, the contents of the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0235] <Material preparation>

[0236] The following materials were prepared.

[0237] (A: cationically polymerizable compound)

[0238] A1: CELLOXIDE 8010 (bis-7-oxabicyclo[4.1.0]heptane, manufactured by Daicel Corporation, epoxy equivalent: about 100 g / eq)

[0239] A2: ETERNACOLL OXBP (4,4'-bis[3-ethyl-3-oxetanyl]methoxymethyl]biphenyl, manufactured by UBE Corporation)

[0240] A3: jER1010 (bisphenol A type solid epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 3000-5000 g / eq, number average molecular weight: 5500)

[0241] A4: jER1007 (bisphenol A type solid epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 1750-2200 g / eq)

[0242] (B: thermal cationic polymerization initiator)

[0243] B1: YH-MS20 (ammonium salt-based thermal cationic polymerization initiator, manufactured by The Yokohama Rubber Co., Ltd.)

[0244] (C: radical polymerizable compound)

[0245] C1: NK ester A-BPEF (9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, manufactured by Shin-Na kamura Chemical Co., Ltd.)

[0246] C2: RIPOXY VR-90 (bisphenol A epoxy methacrylate, manufactured by SHOWA DENKO KK)

[0247] (D: photoradical polymerization initiator)

[0248] D1: Irgacure OXE-02 (1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-ethanone 1-(O-acetyloxime), manufactured by IGM Resins Co., Ltd.)

[0249] (E: Thermoplastic resin)

[0250] · E1: YP-70 (bisphenol A / bisphenol F copolymer phenoxy resin, manufactured by NIPPON STEEL Chemical & Material Co., Ltd., weight average molecular weight: 50,000 to 60,000, Tg: 70 to 80°C)

[0251] E2: Phenoxy resin P-1 synthesized as follows

[0252] (F: coupling agent)

[0253] F1: SH-6040 (γ-glycidyloxypropyltrimethoxysilane, manufactured by Toray Dow Corning Co., Ltd.)

[0254] (G: filling material)

[0255] ·G1: R805 (octylsilane surface treated silica fine particles, manufactured by NIPPON AEROSIL CO., LTD., average particle size: 12 nm)

[0256] (H: heat curing reaction rate regulator)

[0257] H1: ε-caprolactam (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0258] (I: conductive particles)

[0259] I1: Conductive particles having a nickel layer having a thickness of 0.20 μm formed on the surface of a core (particle) made of plastic (cross-linked polystyrene) (average particle size: 3.0 μm, CV value of particle size: 4.2%, specific gravity: 2.5)

[0260] <Synthesis of phenoxy resin P-1>

[0261] 4,4'-(9-fluorenyl)bisphenol 45g (manufactured by Sigma-Aldrich Japan) and 3,3',5,5'-tetramethylbiphenol diglycidyl ether 50g (YX-4000H, manufactured by Mitsubishi Chemical Corporation) were dissolved in 1000mL of N-methylpyrrolidone in a 3000mL three-necked flask equipped with a Dimroth cooling tube, a calcium chloride tube, and a PTFE stirring rod connected to a stirring motor to prepare a reaction solution. 21g of potassium carbonate was added thereto, heated to 110°C using a heating jacket and stirred. After stirring for 3 hours, the reaction solution was added dropwise to a beaker containing 1000mL of methanol, and the precipitate generated was filtered and collected by suction filtration. The precipitate collected by filtration was further washed three times with 300 mL of methanol to obtain 75 g of phenoxy resin P-1 (Mn=15769, Mw=38045, Mw / Mn=2.413). The number average molecular weight Mn and weight average molecular weight Mw of phenoxy resin P-1 are molecular weights in terms of polystyrene measured under the following conditions using a high performance liquid chromatograph GP8020 manufactured by TOSOH CORPORATION.

[0262] [condition]

[0263] Column: Gelpak GL-A150S and GLA160S manufactured by Showa Denko Materials Co., Ltd.

[0264] ·Eluent: Tetrahydrofuran

[0265] Flow rate: 1.0mL / min

[0266] <Preparation of substrate>

[0267] A substrate (PET film, thickness: 55 μm) having a plurality of concave portions on the surface was prepared. The concave portions of the substrate were set to be truncated cone-shaped with the opening area expanding toward the surface side of the substrate (when viewed from above the opening, the center of the bottom is the same as the center of the opening), the opening diameter was set to 4.3 μmφ, the bottom diameter was set to 4.0 μmφ, and the depth was set to 4.0 μm. In addition, the plurality of concave portions of the substrate were formed in a triangular array regular pattern at intervals of 6.2 μm (the distance between the centers of each bottom) to reach 29,000 per 1 mm square.

[0268] <Example 1>

[0269] (Step (I))

[0270] [Formation of Precursor Layer]

[0271] The external stimulus curable composition was prepared by mixing the materials shown in Table 1 into the composition shown in Table 1. The blending amounts in Table 1 indicate the solid content.

[0272] [Table 1]

[0273]

[0274] The obtained external stimulus curable composition was mixed with an organic solvent (2-butanone) to obtain a varnish. Next, the varnish was applied to a PET film with a thickness of 38 μm treated with silicone release, and hot air dried at 60° C. for 3 minutes using an explosion-proof dryer (DFB-80S, manufactured by Futaba Science Co., Ltd.), thereby forming a precursor layer on the PET film. Thus, a laminated film having a PET film and a precursor layer was obtained.

[0275] [Transfer process]

[0276] Conductive particles (I1) are arranged on the surface of the pre-prepared substrate with the concave portion formed thereon, and the excess conductive particles are removed by wiping the surface of the substrate with the concave portion formed thereon with a micro-adhesive roller, so that the conductive particles are arranged only in the concave portion. Next, the substrate is arranged on a heated heating plate (HP-2SA, manufactured by AS ONE CORPORATION) so that the surface of the substrate with the concave portion formed thereon is opposite to the surface on the side of the precursor layer of the laminate film, and the substrate and the laminate film are bonded together using a scraper, and the conductive particles are transferred to the precursor layer. Thus, a laminate film with the first particle having a PET film, a precursor layer, and conductive particles partially embedded in the precursor layer is obtained. In addition, the heating temperature of the above-mentioned heating plate is set to the lowest temperature among the temperatures at which the particle transfer rate to the precursor layer reaches 98% or more.

[0277] [Curing process]

[0278] The precursor layer was irradiated with ultraviolet light from the opposite side of the PET film of the laminated film with the first particles using a UV exposure machine (UVC-2534 1MNLC3-XJ01, manufactured by Ushio Inc.) to react and cure the photocurable components (radical polymerizable compounds and photoradical polymerization initiators) in the precursor layer. Thus, a first adhesive film having a PET film, a first adhesive layer, and conductive particles partially embedded in the first adhesive layer was obtained. In addition, the exposure illuminance was set to 250±10 mW / cm 2 The accumulated light intensity of the light with a wavelength of 350nm is set to 1500±50mJ / cm 2 The exposure illuminance and the integrated light quantity were measured using an ultraviolet integrated light quantity meter (UI T-250, manufactured by Ushio Inc.).

[0279] (Step (II))

[0280] [Preparation of the second adhesive film]

[0281] The second adhesive composition was prepared by mixing the materials shown in Table 2 into the composition shown in Table 2. The blending amounts in Table 2 indicate the solid content.

[0282] [Table 2]

[0283]

[0284] The obtained second adhesive composition was mixed with an organic solvent (2-butanone) to obtain a varnish. Next, the varnish was applied to a PET film with a thickness of 38 μm that had been subjected to a silicone release treatment, and hot air dried at 60° C. for 3 minutes using an explosion-proof dryer (DFB-80S, manufactured by FutabaScience Co., Ltd.), thereby forming a second adhesive layer on the PET film. Thus, a second adhesive film having a PET film and a second adhesive layer was obtained.

[0285] [Lamination process]

[0286] The second adhesive film was attached to the first adhesive layer side of the first adhesive film produced in step (I) from the second adhesive layer side, and the bonding was performed by applying a temperature of 50° C. using a hot roll laminator (Leon13DX, manufactured by LAMI CORPORATION INC.). Thus, the circuit connection adhesive film of Example 1 (circuit connection adhesive film with PET film) was obtained.

[0287] [Measurement of particle embedding rate]

[0288] First, the circuit connection adhesive film is clamped by two pieces of glass (thickness: about 1 mm), and injection molding is performed with a resin composition consisting of 100 g of bisphenol A epoxy resin (trade name: jER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (trade name: Epomount curing agent, manufactured by Refine Tec Ltd.). Next, a cross-section is ground using a grinder to expose the longitudinal section (cross section in the thickness direction) of the circuit connection adhesive film. Next, a scanning electron microscope (SEM, trade name: SE-8020, manufactured by Hitachi High-Tech Corporation) is used to observe at a magnification of 5000 times to obtain a cross-sectional image (SEM image). In any 20 μm×15 μm area in the obtained cross-sectional image, the embedding rate of the conductive particles with the largest particle size L in the embedding direction and the conductive particles with a particle size L of 0.85 to 1.00 times that of the conductive particles is calculated, and their average values ​​are calculated. The same operation was performed on any 100 cross sections, and the average values ​​of the embedding rates of the conductive particles calculated for the respective cross sections were averaged to determine the embedding rate of the conductive particles in the circuit connecting adhesive film (particle embedding rate).

[0289] [Measurement of Average Particle Size and CV Value of Particle Size of Conductive Particles]

[0290] The average particle size and CV value of the particle size of the conductive particles were calculated using the cross-sectional images obtained in the measurement of the particle embedding rate. Specifically, the particle size L of the conductive particles in the embedding direction was measured in any 20μm×15μm area within the obtained cross-sectional image, and their average values ​​and CV values ​​were calculated. The same operation was performed on any 100 cross sections to find the average value of the average particle size of the conductive particles and the average value of the CV value of the particle size calculated for each cross section, and these were set as the average particle size and CV value of the conductive particles in the adhesive film for circuit connection. The average particle size of the conductive particles in the adhesive film for circuit connection is 2.3μm, and the CV value of the particle size is 5.8%.

[0291] [Measurement of thickness]

[0292] In the measurement of the particle embedding rate, the length from the boundary of the first adhesive layer and the second adhesive layer located in the separation portion of the adjacent conductive particles to the respective surfaces was measured using the obtained cross-sectional image, and the thickness of the first adhesive layer, the thickness of the second adhesive layer, and the thickness of the adhesive film for circuit connection were obtained. The thickness of the first adhesive layer in the adhesive film for circuit connection of Examples 1 to 10 was 1.5 μm, the thickness of the second adhesive layer was 3.5 μm, and the thickness of the adhesive film for circuit connection was 5.0 μm.

[0293] [Measurement of flow rate]

[0294] First, the circuit connection adhesive film with a PET film was punched out in the thickness direction using a Trepan BP-10F 1.0 mm (manufactured by KAI INDUSTRIES CO., LTD.) to obtain a disc-shaped evaluation adhesive film having a diameter of 1 mm.

[0295] After peeling off the PET film on the first adhesive layer side from the obtained evaluation adhesive film, the evaluation adhesive film was placed on a cover glass (thickness 0.15 mm, width 18 mm, depth 18 mm) manufactured by Matsunami Glass Ind., Ltd. from the first adhesive layer side, and thermally pressed from the second adhesive layer side using a thermal pressing device LD-06 manufactured by OHASHI SEISAKUSYO Co., Ltd. under the conditions of a pressing temperature of 70° C., a pressing pressure of 0.1 MPa, and a pressing time of 1.0 second, thereby obtaining a temporary fixed body (cover glass / evaluation adhesive film / PET film). In addition, the pressing temperature is the temperature reached when pressing for 1 second, and the pressing pressure is the pressure converted to the area of ​​the evaluation adhesive film.

[0296] Next, after peeling off the PET film on the second adhesive layer side from the temporary fixing body, a cover glass (thickness 0.15 mm, width 18 mm, depth 18 mm) manufactured by Matsunami Glass Ind., Ltd. was placed on the second adhesive layer to obtain a laminate (cover glass / evaluation adhesive film / cover glass). Next, using a hot pressing device FC3000WS manufactured by TORAY ENGINEERING Co., Ltd., the laminate was hot pressed from the second adhesive layer side under the conditions of a pressing temperature of 160°C, a pressing pressure of 2 MPa, and a pressing time of 5 seconds to obtain a pressed body. In addition, the pressing temperature is the highest reached temperature of the evaluation adhesive film, and the pressing pressure is the area conversion pressure of the evaluation adhesive film. The maximum reached temperature was adjusted as follows: a dummy sample (the same laminate as the evaluation laminate) was prepared separately, a thin temperature sensor (ST-50D manufactured by RKC INSTRUMENT INC.) was sandwiched between the adhesive film of the dummy sample and the cover glass on the first adhesive layer side, and the maximum reached temperature of the adhesive film in the dummy sample was measured in advance.

[0297] The pressed body was observed with an optical microscope (L300ND manufactured by Nikon Corporation), and the bonding area S between the surface on the first adhesive layer side of the pressed body and the cover glass was determined using a length measuring tool. B1 (Unit: mm 2 ) and the bonding area S between the surface of the second adhesive layer and the cover glass B2 (Unit: mm 2 ), and the flowability of the first adhesive layer and the flowability of the second adhesive layer were calculated according to the following formula (2-1a) and formula (2-2a). And, based on the obtained flowability, the ratio (flowability ratio) of the flowability of the second adhesive layer 2 to the flowability of the first adhesive layer 1 was calculated. The results are shown in Table 3.

[0298] Flow rate of the first adhesive layer [%] = S B1 / (0.25π)×100···(2-1a)

[0299] Flow rate of the second adhesive layer [%] = S B2 / (0.25π)×100···(2-2a)

[0300] <Example 2>

[0301] A circuit connection adhesive film was obtained in the same manner as in Example 1 except that the amount of the second adhesive composition used and the coating method were changed so that the thickness of the second adhesive layer became 15 μm. Furthermore, the flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3. In addition, it was confirmed that the average particle size and the CV value of the particle size of the conductive particles in the circuit connection adhesive film were the same as those in Example 1.

[0302] <Example 3>

[0303] After the transfer process, the pressurization process was performed before the curing process. Except that the pressurization process was performed in the same manner as in Example 1, an adhesive film for circuit connection was obtained. The pressurization process was performed by arranging a release film (A3171 manufactured by TOYOBO CO., LTD., thickness: 50 μm) obtained by performing a surface release treatment on both sides of the laminated film with the first particles, and then using a hot roll laminator (Leon13DX, manufactured by LAMI CORPORATION INC.) to apply a temperature of 35°C and clamp the obtained laminate. In addition, the flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3. In addition, it was confirmed that the average particle size and CV value of the particle size of the conductive particles in the adhesive film for circuit connection were the same as those in Example 1.

[0304] <Examples 4, 6 to 8>

[0305] The adhesive film for circuit connection was obtained in the same manner as in Example 1 except that the drying time when forming the precursor layer was changed as shown in Table 3. Furthermore, the flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3. In addition, it was confirmed that the average particle size and the CV value of the particle size of the conductive particles in the adhesive film for circuit connection were the same as those in Example 1.

[0306] <Examples 5 and 9>

[0307] The adhesive film for circuit connection was obtained in the same manner as in Example 3 except that the drying time when forming the precursor layer was changed as shown in Table 3. Furthermore, the flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3. In addition, it was confirmed that the average particle size and the CV value of the particle size of the conductive particles in the adhesive film for circuit connection were the same as those in Example 1.

[0308] <Example 10>

[0309] The same method as in Example 3 was used to obtain an adhesive film for circuit connection, except that the drying time when forming the precursor layer was changed to that shown in Table 3 and the heating temperature in the pressurizing step was changed to 50° C. Furthermore, the flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3. In addition, it was confirmed that the average particle size and the CV value of the particle size of the conductive particles in the adhesive film for circuit connection were the same as those in Example 1.

[0310] <Comparative Example 1>

[0311] In the same manner as in Example 1, a laminated film having a PET film and a precursor layer, and a second adhesive film having a PET film and a second adhesive layer were prepared. Next, the second adhesive film was used instead of the laminated film, and the transfer process was performed in the same manner as in Example 1, so that the conductive particles were transferred to the second adhesive layer. Next, the lamination process was performed in the same manner as in Example 1, and the precursor layer was laminated on the second adhesive layer to which the conductive particles were transferred. Next, the curing process was performed in the same manner as in Example 1, and the precursor layer was cured to form the first adhesive layer. Thus, an adhesive film for circuit connection was obtained. In addition, the flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3.

[0312] <Comparative Example 2>

[0313] A circuit connection adhesive film was obtained in the same manner as in Comparative Example 1 except that a pressurizing step was performed after the transfer step and before the lamination step. The pressurizing step was performed in the same manner as in Example 3. Furthermore, flow rate and the like were measured in the same manner as in Example 1. The results are shown in Table 3.

[0314] <Evaluation>

[0315] (Fabrication of Circuit Connection Structure)

[0316] Using each of the adhesive films for circuit connection obtained above, a connection structure was produced by the following method.

[0317] First, a circuit substrate was prepared in which an ITO circuit electrode (pattern width of 20 μm, inter-electrode space of 10 μm) was formed on the surface of a glass substrate (manufactured by Corning Incorporated: #1737, 38 mm × 28 mm, thickness of 0.5 mm). Next, the circuit connection adhesive film was cut into a 2.0 mm × 2.0 mm square, and after peeling off the PET film on the first adhesive layer side of the circuit connection adhesive film, the first adhesive layer of the circuit connection adhesive film was brought into contact with the surface of the circuit substrate on which the circuit electrode was formed, and the circuit connection adhesive film was temporarily crimped to the circuit substrate to obtain a temporary crimped body. The temporary crimping was performed by heating and pressurizing the circuit connection adhesive film for 1 second under the conditions of an actual measured maximum reached temperature of 70°C and an adhesive film area conversion pressure of 1 MPa. After the temporary crimping, the PET film on the second adhesive layer side was clamped with tweezers and peeled off from the second adhesive layer. Next, an IC chip (with an outer size of 0.5 mm×0.5 mm, a thickness of 0.4 mm, and a bump electrode area of ​​400 μm) having bump electrodes arranged thereon was prepared. 2 After aligning the positions of the bump electrodes of the IC chip and the circuit electrodes of the glass substrate (20 μm in length × 20 μm in width), the second adhesive layer was attached to the IC chip by heating and pressing for 5 seconds under the conditions that the actual measured maximum reaching temperature of the circuit connection adhesive film was 160°C and the area conversion pressure on the bump electrode was 125 MPa. Thus, a circuit connection structure was obtained.

[0318] (Evaluation of Circuit Connection Structure)

[0319] The connection resistance and particle capturing property of each circuit connection structure obtained above were evaluated by the following methods.

[0320] [Connection resistance evaluation]

[0321] The connection resistance was evaluated by measuring the resistance between the opposing electrodes of the circuit connection structure (between the bump electrode and the circuit electrode) using a four-terminal measurement method using a multimeter (MLR21, manufactured by Kusumoto Chemicals, Ltd.) and comparing the average value of the measured values ​​at 14 locations (initial installation resistance value).

[0322] [Particle capture performance evaluation]

[0323] The appearance (installation appearance) of the temporary press-bonded body and the circuit connection structure was observed from the glass substrate side using a differential interference microscope to evaluate the capture of conductive particles. Specifically, first, the area in contact with a 100 μm × 100 μm square area containing 9 IC chip bump electrodes was observed at any 5 locations of the temporary press-bonded body, the number of conductive particles contained in the area was counted, and the average value v of the number of conductive particles obtained at the 5 locations was calculated. A1 Next, for the circuit connection structure obtained from the observed temporary crimped body, the number of conductive particles contained in the same area as the observed part of the temporary crimped body (5 parts) was counted, and the average value v of the number of conductive particles obtained in the 5 parts was calculated. A2 Next, based on the average value v of the number of conductive particles obtained for the temporary crimped body, A1 and the average value v of the number of conductive particles obtained for the circuit connection structure A2 , the particle residual rate x(v A2 / v A1 × 100). Based on the obtained particle residual rate x, the capturing performance of the conductive particles was evaluated according to the following criteria.

[0324] 5: x ≥ 98%

[0325] 4: 90% ≤ x < 98%

[0326] 3: 75% ≤ x < 90%

[0327] 2: 50% ≤ x < 75%

[0328] 1: x<50%

[0329] [Table 3]

[0330]

[0331] In Table 3, the particle transfer layer indicates a layer to which the conductive particles are transferred in the transfer step, and the drying time indicates the drying time when the transfer layer is formed.

[0332] Explanation of symbols

[0333] 1-first adhesive layer, 2-second adhesive layer, 3-conductive particles, 10-adhesive film for circuit connection, 10-adhesive film for circuit connection, 11-precursor layer, 15-first adhesive film, 16-second adhesive film, 22-base, 31-first circuit substrate, 32-first electrode (circuit electrode), 33-first circuit component, 34-second circuit substrate, 35-second electrode (bump electrode), 36-second circuit component, 40-connecting portion, 100-connecting structure.

Claims

1. An adhesive film for circuit connection, comprising: The first adhesive layer is thermosetting; Conductive particles are partially embedded in one side of the first adhesive layer; and a second adhesive layer having thermosetting properties and in contact with the one surface of the first adhesive layer, The embedding rate of the conductive particles in the first adhesive layer obtained by the following formula (1) is 30 to 90%. The circuit connection adhesive film is placed on a glass plate from the first adhesive layer side, and temporary pressing is performed under the conditions of a pressing temperature of 70° C., a pressing pressure of 0.1 MPa, and a pressing time of 1.0 s. Then, a glass plate is placed on the second adhesive layer, and formal pressing is performed under the conditions of a pressing temperature of 160° C., a pressing pressure of 2 MPa, and a pressing time of 5 s. The flow rate of each adhesive layer during the pressing is defined by the following formula (2), and the ratio of the flow rate of the second adhesive layer to the flow rate of the first adhesive layer is 1.20 to 4.

00. Embedment rate (%) = H / L × 100 (1), In formula (1), H represents the embedding length of the conductive particles in the first adhesive layer (unit: μm), L represents the particle size of the conductive particles in the embedding direction (unit: μm), Flow rate [%] = S B / S A ×100···(2), In formula (2), S A It represents the surface area of ​​the adhesive layer before temporary crimping, S B Indicates the area of ​​the adhesive layer after full crimping.

2. The circuit connection adhesive film according to claim 1, wherein: The flow rate of the first adhesive layer is 88 to 110%.

3. The circuit connection adhesive film according to claim 1 or 2, wherein: The first adhesive layer is a cured product of a precursor layer containing an external stimulus curable composition.

4. The circuit connection adhesive film according to claim 3, wherein: The external stimulus curable composition has photocurability.

5. The circuit connection adhesive film according to claim 1 or 2, wherein: At least a portion of the plurality of conductive particles are arranged in a predetermined pattern in a plan view.

6. The adhesive film for circuit connection according to claim 1 or 2, wherein: The average particle size of the conductive particles is 1.0 to 50.0 μm. The CV value of the particle size of the conductive particles is 25% or less.

7. The adhesive film for circuit connection according to claim 1 or 2, wherein: The ratio of the thickness of the circuit-connecting adhesive film to the average particle diameter of the conductive particles is 1.1 to 10.

0.

8. The adhesive film for circuit connection according to claim 1 or 2, wherein: The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer is 0.3 to 20.

0.

9. A method for manufacturing the circuit connection adhesive film according to claim 1, comprising: Step (I) of preparing a first adhesive film including the first adhesive layer and the conductive particles partially embedded in one side of the first adhesive layer; and Step (II), providing the second adhesive layer on the one side of the first adhesive layer, The step (I) includes a curing step of curing the precursor layer by external stimulation to form the first adhesive layer in a state where the conductive particles are partially embedded in one surface side of the precursor layer including the external stimulation curable composition.

10. The method for producing an adhesive film for circuit connection according to claim 9, wherein: In the curing step, the precursor layer is cured so that the flow rate of the first adhesive layer reaches 88 to 110%.

11. The method for producing an adhesive film for circuit connection according to claim 9 or 10, wherein: The external stimulus curable composition has photocurability, In the curing step, the precursor layer is cured by light irradiation.

12. The method for producing an adhesive film for circuit connection according to claim 9 or 10, wherein: The step (I) further includes a transfer step of transferring the conductive particles from the substrate to the precursor layer by providing the precursor layer on a surface of a substrate on which a plurality of conductive particles are arranged.

13. The method for producing an adhesive film for circuit connection according to claim 12, wherein: The step (I) further includes a heating step of heating the layer containing the external stimulus curable composition at 50 to 70° C. for 3 to 60 minutes before the transfer step.

14. The method for producing an adhesive film for circuit connection according to claim 12, wherein: The step (I) further includes, after the transfer step, a pressurizing step of applying pressure to the surface of the precursor layer to which the conductive particles are transferred.

15. A connection structure, comprising: a first circuit component having a first electrode; a second circuit component having a second electrode electrically connected to the first electrode; and a connection portion for electrically connecting the first electrode and the second electrode to each other via conductive particles and for bonding the first circuit component and the second circuit component to each other. The connecting portion includes a cured product of the circuit-connecting adhesive film according to claim 1 or 2.

16. A method for manufacturing a connection structure, comprising the following steps: The circuit-connecting adhesive film according to claim 1 or 2 is disposed between a surface of a first circuit member having a first electrode and provided with the first electrode and a surface of a second circuit member having a second electrode and provided with the second electrode; and The stack including the first circuit component, the circuit connection adhesive film and the second circuit component is heated while being pressed in the thickness direction of the stack, thereby electrically connecting the first electrode and the second electrode to each other via conductive particles and bonding the first circuit component to the second circuit component.

Citation Information

Patent Citations

  • Anisotropic conductive adhesive sheet and coupling structure

    WO2005054388A1